Pemberdayaan dan Pemanfaatan Lahan Pertanian dalam Meningkatkan Hasil Panen Masyarakat RT 36 Kelurahan Karang Joang - Christopher Davito Prabandewa Hertadi; Mochamad Sulaiman; Putri Gesan Prabawa Anwar; Ageng Margyatno; Nisa' Nur Halimah; Syahdan Nugroho; Aqmal Rizaqi; Nisa' Nur Azizah; Tio Putra Permadi; Ayumi Devidhavyasa (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
RT area. 36 is located in North Balikpapan with some of its residents working as vegetable farmers on plantations. One of the problems faced in RT. 36 is a hard and dry soil condition. This has an impact on hampering planting in the form of decreased crop yields and even crop failure. The water level in the soil during the dry season tends to be so low that plants cannot survive. This problem gave rise to a solution in the form of designing an automatic watering machine to improve the quality and water content of the soil for planting as well as innovating automated technology to control agricultural land conditions using a timer. Previous soil conditions experienced drought and poor soil with a water content of 10%-20%, 50% microorganisms which could hinder agriculture by increasing the risk of crop failure. After using an automatic watering device, it can increase soil water content by 30%-50%, microorganisms by 20%-30%, so that it can increase crop yields by 20% in various seasons and improve the quality of the harvest.